Rest 2D speckle tracking echocardiography may be a sensitive but nonspecific test for detection of significant coronary artery disease - Mahjoob, Mohammad Parsa; Alipour Parsa, Saeed; Mazarei, Asghar; Safi, Morteza; Khaheshi, Isa; Esmaeeli, Shooka (Acta Biomedica Atenei Parmensis, 2018)
Aims: To detect the significance of coronary artery disease in the patients, who are suspected, was assumed to be one of the advantages of 2D STE, as a novel non-invasive imaging modality with acceptable accuracy. Methods: In this study, 216 patients who were suspected to have coronary artery disease and candidate for coronary angiography, underwent rest two-dimensional speckle tracking echocardiography (2D STE) and negative global systolic longitudinal strain was evaluated. Results: Negative global systolic left ventricular longitudinal strain under 18% in rest 2D-STE was significantly prevalent in patients with significant CAD in coronary angiography (P value<0.0001).Our results revealed sensitivity of 91.1%, specificity of 63.0%, positive predictive value of 80.4%, negative predictive value of 81.0% and accuracy of 80.5% for rest 2D-STE in detection of significant CAD. Conclusion: Here in we showed that rest Two-dimensional speckle tracking echocardiography could be a sensitive but nonspecific imaging modality to determine significant coronary artery disease. Future studies with large size will reveal more detailed findings.